Synthesis, Physical Characterization of M(III) Transition Metal Complexes Derived from Thiodihydrazide and 5-tert-Butyl-2-hydroxy-3-(3-phenylpent-3-yl) Benzaldehyde. Issue 4 (2012) - Kumar, Gajendra; Johari, Rajeev; Devi, Shoma
Abstract : A Schiff base ligand was synthesized by reacting 5-tert-butl-2-hydroxy-3-(3-phenylpent-3-yl) benzaldehyde and thiodihydrazide (2:1) and a series of metal complexes with this new ligand were synthesized by reaction with Cr (III), Mn (III), and Fe (III) metal salt in methanolic medium. The Schiff base ligand and its complexes have been characterized with the help of elemental analysis, conductance measurements, magnetic measurements and their structure configuration have been determined by various spectroscopic (electronic, IR, 1 H NMR, 13 C NMR, GCMS) techniques. Electronic and magnetic moments of the complexes indicate that the geometries of the metal centers were octahedral. IR spectral data suggest that ligand behaves as a tetradentate ligand with ONNO donor sequence towards the metal ion.